نطاق تطبيق حرية المنافسة في إبرام العقود الإدارية دراسة مقارنة - حسين, أ.م.د. مصطفى رسول; صادق, بەسۆز شريف (Sulaimani Journal for Humanities, 2023)
There are a number of principles applicable to the administrative contracts, the most important of which is the principle of free competition to participate, which is a guarantee for the principle of equality and integrity of administrative contracts However, in some cases the scope of the application of this principle in public contracts is restricted or eliminated without excluding the contractor due to penal texts or administrative decisions in the public interest. In this paper, we will discuss the introduction of the principles and discrimination based on the principle in administrative contracts.
Keywords: Administrative law; administrative contracts; the principle of competition; the public interest